(untitled) - Mannino, Michael V. (New York, 2007)
Mannino's "Database Management" provides the information you need to learn relational databases. The book teaches students how to apply relational databases in solving basic and advanced database problems and cases. The fundamental database technologies of each processing environment are presented; as well as relating these technologies to the advances of e-commerce and enterprise computing. This book provides the foundation for the advanced study of individual database management systems, electronic commerce applications, and enterprise computing.
Keywords: Database design,Thiết kế Cơ sở dữ liệu,Application software,Database management,Ứng dụng phần mềm,Quản trị cơ sở dữ liệu